Visual representations of Iraqi refugees in Deutsche Welle / Alsawad Nooruldeen Fernas Jumaah - Alsawad Nooruldeen, Fernas Jumaah (2019)
This study perused the visual representation of the Iraqi refugees in the online German newspaper DW during the period between 2014 and 2017, when a huge number of refugees have fled their houses seeking for safe harbour. The study determined the various semiotic resources utilized in conveying images of the Iraqi refugees to viewers and to investigate how the German newspaper DW portrayed the Iraqi refugees. Sixteen images collected from the online German newspaper DW were used for analysis. Two frameworks were used to perform a semiotic analysis of the visual elements: Kress and Van Leeuwen (1996) of social representation and Van Leeuwen (2008) for the representation of the social actors. These frameworks were utilized as investigative tools to show how the Iraqi refugees are depicted, respectively in two steps of analysis. The findings revealed that the Iraqi refugees were pictured as victims and criminals in different situations in the images during the time period from 2014 to 2017. The way of representing refugees throughout these four years has slightly changed along with the political changes occurring in Germany during this period. Additionally, it was shown that the Iraqi refugees who are featured in the images published by DW newspaper were multi-religious, (Muslims, Christians and Yazidis). The study also found that the Iraqi refugees in 2014 were visually represented in groups, focusing mostly on women and children, in contrast with the method of depiction in 2017 where the represented participants were mostly adults and given individual characteristics. In addition, these findings illustrated some similarities in the way of representing the Iraqi refugees throughout the selected period.